THE ETHICS OF SCIENTIFIC RESEARCH (WITH PARTICULAR EMPHASIS ON EXERCISE AND MOVEMENT SCIENCE) (English translated version) - Aragón-Vargas, Luis Fernando (Pensar en Movimiento: Revista de Ciencias del Ejercicio y la Salud, 2015)
This paper reviews how we arrived at the current state of affairs in the ethical practice of scientific research, discussing some issues that are particularly pertinent to the exercise scientist. The paper focuses on two major areas of ethics in science. The ethical principles for biomedical research involving human subjects are presented and discussed using the three basic principles from the Belmont Report (autonomy, beneficence, and justice) as a guide. The ethical presentation and publication of data are discussed as an update or expanded comment on the ten topics covered by Roy Shephard in his Ethics in Exercise Science Research paper from 2002. The manuscript closes with a reflection on personal responsibility and its importance in every scientific endeavor: placing all responsibility for action on those scientists or physicians doing the experiments was not sufficient to prevent all types of human research abuses in the first half of the twentieth century. However, intricate and cumbersome external review and approval procedures generate the perception that the system should be more than enough to ensure good practices, a perception that may dangerously prevent the scientists from assuming their individual responsibility.